Pengetahuan Ibu Hamil Mengenai Penyakit Herediter: Thalassemia - Ganis Indriati; Riri Novayelinda; Yufitriana Amir; Widia Lestari; Misrawati; Nurhayati; Danu Mangippu Pasaribu; Ruth Pratiwi Nathasya Manurung (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2026)
Introduction: Hereditary diseases are conditions passed from parents to their children through genetic inheritance from early pregnancy. One such condition requiring significant attention is thalassemia, a genetic blood disorder with a substantial economic burden in Indonesia, ranking fifth among non-communicable diseases. Children with thalassemia major require lifelong blood transfusions and iron chelation therapy, resulting in high healthcare costs. Despite this, public knowledge—especially among pregnant women—remains limited, although screening during pregnancy is feasible and essential for early detection and subsequent decision-making. Objectives: This study aimed to assess pregnant women’s knowledge regarding hereditary disease, specifically thalassemia. Methods: A descriptive cross-sectional design was employed, conducted over six months in the working area of Umban Sari Health Center, Meranti Pandak, Pekanbaru. Samples were selected through purposive sampling, and data were collected using a questionnaire on thalassemia. The results were analyzed descriptively and presented in frequency distribution tables. Results: The findings indicated that most respondents (66 participants; 85.7%) had poor knowledge of thalassemia, while a small proportion demonstrated moderate knowledge, and none showed good knowledge. This lack of awareness may be influenced by the respondents’ employment status, as the majority (96.1%) were housewives with limited exposure to health information. Additionally, the low prevalence of thalassemia in the general population may contribute to limited awareness. Conclusion: Pregnant women’s knowledge of thalassemia remains low, emphasizing the need for strengthened health education and targeted awareness programs to support early screening and informed decision-making.